Hubungan Kepatuhan Ibu Dalam Mengkonsumsi Tablet Fe Dengan Kejadian Anemia Dalam Kehamilan Di Puskesmas Ingin Jaya Kabupaten Aceh Besar - Aryani, Roza (Universitas Muhammadiyah Surabaya, 2022)
Objective: Compliance is one of the important factors that determine the success of the program. A person is said to be obedient if the person is willing to follow and obey the rules or policies and has been determined without any coercion and demands from others. The World Health Organization (WHO) reports that the prevalence of pregnant women with iron deficiency is around 35-75%, and it increases with increasing gestational age.Methods: This research is analytic with cross sectional approach . The population in this study were pregnant women who were at the Want Jaya Public Health Center, Aceh Besar District, as many as 82 respondents with non-probability sampling technique.Results: obtained _value is 0.024, then a test is carried out where _value is0.024 <0.05, so it can be seen that the hypothesis (Ho) is rejected, this shows a relationship between adherence to consuming Fe tablets and the incidence of anemia in pregnancy at the Want Jaya Health Center, Aceh Besar District .Conclusion: Based on the results of research that has been carried out at the Want Jaya Health Center, Want Jaya Regency, Aceh Besar Regency, with the incidence of anemia at the Want Jaya Health Center, Aceh Besar District, the researcher can conclude that, out of 82 respondents, the majority of mothers experienced anemia, namely 64 respondents (79 %), and pregnant women who are categorized as non-compliant are 64 respondents (78.0%). _value 0.024<0.05 There is an influence between maternal adherence to Fe tablets and the incidence of anemia at the WantJaya Public Health Center, Aceh Besar District.